Preparation and Characterization of Maleic Anhydride Grafted Poly(Hydroxybutirate-CO-Hydroxyvalerate) – PHBV-g-MA - Montanheiro,Thaís Larissa do Amaral (2016)
A compatibilizer agent was successfully produced by grafting maleic anhydride (MA) to poly(hydroxybutyrate-co-hydroxyvalerate) (PHBV) chains on a reactive processing by mechanical mixing, using a mixture of PHBV, MA and dicumyl peroxide (DCP) as initiator. The resulting PHBV grafted MA (PHBV-g-MA) was characterized by Fourier transform infrared (FTIR) spectroscopy, thermogravimetric analysis (TGA), differential scanning calorimetry (DSC) and gel permeation chromatography (GPC), and its properties were compared to neat PHBV. FTIR showed an absorption band at 699 cm-1 for PHBV-g-MA, related to CH group of grafted anhydride ring. The initial thermal degradation temperature of the compatibilizer agent was reduced when compared to neat PHBV. DSC analysis showed that after grafting MA onto PHBV the crystallization temperature was about 20ºC higher than neat PHBV, and the degree of crystallinity was increased. GPC analysis showed that MA when grafted onto PHBV led to a reduction of molecular weight and polydispersity.